2020
DOI: 10.1038/s41598-020-68204-x
|View full text |Cite
|
Sign up to set email alerts
|

Are choriocapillaris flow void features robust to diurnal variations? A swept-source optical coherence tomography angiography (OCTA) study

Abstract: We evaluated the impact of diurnal variation on choroidal and retinal microvasculature and structural measurements using a swept-source optical coherence tomography angiography machine (SS-OCTA; PLEX Elite 9,000, Carl Zeiss Meditec, Inc., Dublin, USA). Fourteen participants who were without ocular diseases underwent SS-OCTA imaging using 3 × 3-mm 2 macular scan pattern on two separate days at five time points. Choriocapillaris flow voids were generated to determine its density (percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…[61][62][63] The choroidal LA fluctuates in parallel with the diurnal variation in ChT during the day, 64 but the CcFD are not influenced by the diurnal rhythm. 65 Even though the rhythms of AL and ChT in humans could be disturbed by exposure to about 2.00 D myopic or hyperopic defocus for 12 hours during the day, they returned to normal during the second day after removal of the lenses. 51,52 In our present study, the subjects underwent a 20-minute washout period, during which they were exposed to controlled viewing conditions while wearing full optical corrections.…”
Section: Discussionmentioning
confidence: 97%
“…[61][62][63] The choroidal LA fluctuates in parallel with the diurnal variation in ChT during the day, 64 but the CcFD are not influenced by the diurnal rhythm. 65 Even though the rhythms of AL and ChT in humans could be disturbed by exposure to about 2.00 D myopic or hyperopic defocus for 12 hours during the day, they returned to normal during the second day after removal of the lenses. 51,52 In our present study, the subjects underwent a 20-minute washout period, during which they were exposed to controlled viewing conditions while wearing full optical corrections.…”
Section: Discussionmentioning
confidence: 97%
“…The total number of flow deficits were counted, and average sizes computed as the total sizes of flow deficits divide by the total number. Flow deficits metrics showed high inter-session repeatability in normal individuals: in terms of Pearson's R of 0.96 and intraclass correlation coefficients of 0.98 (95% CI, 0.93-0.99) 44 .…”
Section: Measurement Of Choriocapillaris Flow Deficitsmentioning
confidence: 97%
“…The SS-OCTA allows a high-resolution 3-dimensional visualization of perfused microvasculature in a non-invasive manner and characterizes vascular information at the retinal and choriocapillaris layers (Supplementary Figure S3). Participants underwent a 3.0 × 3.0-mm 2 macular centered imaging using the SS-OCTA (PLEX Elite 9000, Carl Zeiss Meditec, Inc., Dublin, USA; Version 1.7) 44 . The OCTA machine provided a signal strength index, ranging from 0 to 10, where only images with a scan quality of 8 and above were accepted.…”
Section: Examination Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific optical coherence tomography angiography (OCTA) studies have already shown the extent of the fluctuations occurring in diurnal retinal vessel density (VD) in patients with various types of glaucoma (1)(2)(3)(4)(5)(6)(7)(8)(9). Several studies have indicated a substantial change in retinal VD; some have demonstrated a continuing decline in retinal VD throughout the day (2,4).…”
Section: Introductionmentioning
confidence: 99%